2007
DOI: 10.2754/avb200776010017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cholecystokinin-Octapeptide and Cerulein on Phasic and Tonic Components in Ovine Duodenum with Special Reference to the 'Minute Rhythm'

Abstract: Cholecystokinin (CCK) can affect phasic contractions and the minute rhythm (MR) in ovine duodenum but its effect on the tonic component remains unclear. Thus, the aim of this study was to assess whether the hormone exerts significant changes on phasic and tonic components of the duodenal motor activity and on phasic and tonic components of the duodenal MR. Mechanical and electrical activities of the duodenum were recorded in four sheep before and after slow intravenous cholecystokinin octapeptide (CCK-OP, dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The MR was observed in sheep, in the several own studies (Romański, 2002;2007;2009b;2010) and in the studies on sheep and calf reported by others (Fleckenstein et al, 1982;Poncet & Ivan, 1984;Ruckebusch, 1989). Therefore, the MR represents the well-established motility pattern.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The MR was observed in sheep, in the several own studies (Romański, 2002;2007;2009b;2010) and in the studies on sheep and calf reported by others (Fleckenstein et al, 1982;Poncet & Ivan, 1984;Ruckebusch, 1989). Therefore, the MR represents the well-established motility pattern.…”
Section: Discussionmentioning
confidence: 76%
“…Such variability has resulted clearly also from the other studies and it was dependent on the animal species, site of occurrence (i.e. the gastrointestinal segment), and feeding conditions (Fleckenstein et al, 1982;Romański, 2002;2007).…”
Section: Discussionmentioning
confidence: 97%
“…This problem was briefly discussed earlier (Romański, 2004) and it was clear that this question should be dealt with separately for each gastrointestinal region. The essential corollaries emerging from the previous study concerning the ovine duodenum pointed out that the equipotent doses of cerulein and CCK-OP oscillate between 1:8 and 1:15 (Romański, 2007b). This remains in concert only with that part of the present study where CCK-OP, administered at a 20 times higher dose than cerulein, exerted a stronger effect and comprised the inhibition of myoelectric activity in the duodenal bulb and the duodenum, but not stimulatory changes, although the differences were not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…However, the opposite and dual effects of CCK-OP and its amphibian analogue, cerulein, have been reported (Giuliani et al, 1990;Martins et al, 2006). In sheep, CCK peptides also inhibit the arrival of the MMC in the upper small intestine, but their effect on intestinal motility has not been fully elucidated so far in spite of several studies performed (Bueno and Praddaude, 1979;Cottrell and Iggo, 1984;Ormas et al, 1984;Onaga et al, 1997;Romański, 2004Romański, , 2007b. Thus the dual effect of CCK upon the small-intestinal motility can also be expected in sheep.…”
mentioning
confidence: 97%
“…However, opposite and dual effects of CCK-OP and cerulein have also been reported (Giuliani et al, 1990). In sheep, CCK affects the small-intestinal myoelectric and motor activity and also inhibits the arrival of the MMC in the upper small intestine, but despite several studies, its effect on intestinal motility has not been fully elucidated so far (Bueno and Praddaude, 1979;Romański, 2004Romański, , 2007aRomański, , 2007b. CCK is usually applied as CCK-octapeptide (CCK-OP), the natural CCK form present in sheep (Titchen, 1986) and it was applied here.…”
mentioning
confidence: 99%